Applying ADDIE Framework in Enhancing ABM Teachers Instructional Strategies in District II, Quezon City - Catabona, Ladylee (Journal of Interdisciplinary Perspectives, 2025)
This Master's thesis by Ladylee V. Catabona, conducted at the Polytechnic University of the Philippines in 2025, investigates the application of the ADDIE (Analysis, Design, Development, Implementation, Evaluation) instructional design framework to enhance the teaching strategies of all Accountancy, Business, and Management (ABM) teachers in District II, Quezon City. The study addresses the absence of a unified instructional framework in the district. Employing a descriptive quantitative methodology, a validated questionnaire assessed teachers' utilization of the ADDIE model, exploring variations based on gender, years of experience, highest educational attainment, and performance (as measured by the IPCRF). Results revealed a predominantly female teaching force (72.09%), with a significant portion having less than 10 years of experience and holding a Master's degree with units. While teachers demonstrated strong skills across all ADDIE phases, minor differences emerged based on experience and educational attainment, with higher educational levels correlating with more consistent application of the ADDIE model. No significant gender-based differences were found. The study concludes that while ABM teachers effectively utilize many aspects of ADDIE, targeted professional development should focus on enhancing collaborative development practices and tailoring opportunities to address the specific needs of teachers based on their experience and educational background. The research provides valuable insights for improving ABM instruction in the district and potentially beyond.